Red light electroluminescent device based on metal nanoclusters and preparation method thereof

By combining metal nanocluster Au6Cu2 with the host material TCTA and OXD-7, and introducing a LiF insulating layer between the emission layer and the electron transport layer, the low glass transition temperature and current carrying capacity of metal nanocluster electroluminescent devices are solved. Subtransmission balancing problem achieves red photoelectroluminescent devices with high brightness and high external quantum yield.

CN119451519AActive Publication Date: 2025-02-14JILIN UNIVERSITY
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411547329.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-02-14
Estimated Expiration
2044-11-01

AI Technical Summary

Technical Problem

The glass transition temperature of existing metal nanocluster electroluminescent devices is low, which leads to the need to preferential choice of spin coating in nanofilm growth processes, and the main materials with high-energy structures lead to carrier transfer balance and exciton confined domains. Problem, affecting the external quantum efficiency and electrical parameters of the device.

Method used

By using metal nanocluster Au6Cu2 and mixed host materials TCTA and OXD-7, a red photoelectroluminescent device is constructed, using the host-guest mixed solution as the emission layer, and an ultra-thin electroinert functional layer LiF is introduced between the emission layer and the electron transport layer. , regulates energy transfer paths and limits exciton composite regions.

Benefits of technology

The device is achieved with high brightness and high external quantum yield, with brightness reaching 3887cd m-2 and an external quantum efficiency reaching 1.55%. The current density is significantly reduced through the introduction of LiF and the stability of the device is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119451519A_ABST
    Figure CN119451519A_ABST
Patent Text Reader

Abstract

The invention is applicable to the technical field of luminescent devices, and provides a preparation method of a red light electroluminescent device based on metal nanoclusters, which comprises the following steps: dissolving thiophane gold and 4 '-ethynylbenzo 15-crown-5 in a dichloromethane solution; dropwise adding a triethylamine solution, volatilizing the solvent, and re-dissolving with a dichloromethane solution to obtain an orange red solution; sealing, carrying out diffusion crystallization, and collecting orange red needle-like crystals; dissolving the orange red acicular crystal and Cu (NCMe) 4PF6 in a dichloromethane solution to obtain a transparent red solution; sealing, carrying out diffusion crystallization, and collecting red needle-like crystals; dissolving the red acicular crystal in a dichloromethane solution containing TCTA and OXD-7 to obtain a subject-object mixed solution; and preliminarily preparing the cluster red light electroluminescent device modified by the subject, the object and the insulating layer: transferring the product into a vacuum cavity, and sequentially depositing an ultrathin LiF layer, a PO-T2T layer, a LiF layer and an Al layer. According to the red light electroluminescent device, the brightness is obviously improved, the external quantum efficiency is high, and the device stability is good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of light-emitting devices, and in particular relates to a red light electroluminescent device based on metal nanoclusters and a preparation method thereof. Background Art

[0002] Metal nanoclusters have many advantages such as high photoluminescence quantum yield (PLQY), low toxicity, and simple synthesis. The special inorganic-organic hybrid environment brought by their core-shell structure gives them a highly controllable excited state composition, making it easier for their luminescence band to cover the visible light-near infrared I region (400nm-900nm).

[0003] However, the special structure of organic ligand-inorganic metal core causes the glass transition temperature (Tg) of most metal nanoclusters to be lower than 200°C, so spin coating should be preferred in the growth process of nanofilms. The unique nano-size of metal nanoclusters requires them to hybridize with the host material and enter the host-guest doped film as a dopant. However, when using a host material with a high energy level structure, carrier transport balance and exciton confinement are engineering issues that need to be considered, because they determine the utilization efficiency of electric excitons, which in turn affects the key electrical parameters of the device, such as external quantum efficiency, current power and power efficiency.

[0004] Therefore, on the premise of formulating a reasonable host-guest material system, how to rationally utilize the functional layer to regulate the energy transfer path and limit the carrier recombination area has become an industrial technical problem that needs to be urgently solved to further improve the metal nanocluster electroluminescent devices. Summary of the invention

[0005] The purpose of the embodiments of the present invention is to provide a method for preparing a red light electroluminescent device based on metal nanoclusters, aiming to solve the problems raised in the above background technology.

[0006] The embodiment of the present invention is implemented as follows: a method for preparing a red light electroluminescent device based on metal nanoclusters comprises the following steps:

[0007] S1. Dissolve tetrahydrothiophene gold and 4'-ethynylbenzo-15-crown-5 in dichloromethane solution and stir until completely dissolved;

[0008] S2, dropwise adding triethylamine solution, stirring at low temperature, evaporating the solvent and re-dissolving it with dichloromethane solution to obtain an orange-red solution;

[0009] S3, sealing the orange-red solution at low temperature, using n-hexane for diffusion crystallization, and collecting the orange-red needle-shaped crystals after standing;

[0010] S4, dissolving the orange-red needle-shaped crystals and powdered Cu(NCMe)4PF6 in a dichloromethane solution, stirring in the dark to obtain a transparent red solution;

[0011] S5, seal the transparent red solution at low temperature, diffuse and crystallize it with ether, and collect the red needle-shaped crystals after standing;

[0012] S6, dissolving the red needle-shaped crystals in a dichloromethane solution containing an electron acceptor material TCTA and an electron donor material OXD-7 to obtain a host-guest mixed solution;

[0013] S7. Preliminary preparation of cluster red electroluminescent devices modified with host, guest and insulating layer:

[0014] S71, cleaning the ITO conductive glass and performing ultraviolet ozone treatment;

[0015] S72, spin coating a PEDOT:PSS solution on the ITO glass, annealing the solution to obtain a hole injection layer, and then transferring the solution to a glove box filled with N2 gas;

[0016] S73, spin coating the host-guest mixed solution on the PEDOT:PSS layer as a light-emitting layer;

[0017] S8. Transfer the product obtained in S7 into a vacuum chamber, and deposit ultra-thin LiF, PO-T2T, LiF and Al layers in sequence by thermal evaporation, wherein the ultra-thin LiF serves as an insulating layer, the PO-T2T layer serves as an electron transport layer and a hole blocking layer, and the LiF and Al layers serve as top electrodes, thereby obtaining the red electroluminescent device based on metal nanoclusters.

[0018] Preferably, in S1, the stirring speed is 800-1000 r / min, and the time is 8-10 min.

[0019] Preferably, in S2, the stirring speed is 600-800 r / min, the volatile solvent is evaporated using a rotary evaporator, the speed during rotary evaporation is 80-100 r / min, and the temperature is 23-28°C.

[0020] Preferably, in S4, the stirring speed is 800-1000 r / min.

[0021] Preferably, in S6, the concentration of red crystals in the host-guest mixed solution is 2.0 mg / mL, the concentration of TCTA is 4.0 mg / mL, and the concentration of OXD-7 is 3.5 mg / mL;

[0022] After the step of dissolving the red needle-shaped crystals in the dichloromethane solution containing the electron acceptor material TCTA and the electron donor material OXD-7, the method further includes the steps of vigorous shaking for 1-2 minutes and ultrasonic treatment for 1-2 minutes.

[0023] Preferably, in S71, the step of cleaning the ITO conductive glass is specifically: cleaning the ITO conductive glass with soap, deionized water, ethanol, chloroform, acetone and isopropanol in sequence.

[0024] Preferably, in S72, the rotation speed of the spin coating PEDOT:PSS solution is 3800-4200 r / min, and the rotation time is 28-32 s;

[0025] The annealing treatment is performed at a temperature of 165-175° C. and for a time of 25-35 minutes.

[0026] Preferably, in S73, the rotation speed of spin coating the host-guest mixed solution on the PEDOT:PSS layer is 2800-3200 r / min, and the rotation time is 38-32 s.

[0027] Preferably, in S8, the evaporation rates of the ultra-thin LiF, PO-T2T and LiF are 0.05-0.2 nm / s, and the thicknesses are 0.5 nm-2 nm, 30-50 nm and 1-2 nm respectively; the evaporation rate of Al is 1-3 nm / s, and the thickness is 100-120 nm.

[0028] Another object of an embodiment of the present invention is to provide a red electroluminescent device based on metal nanoclusters prepared by the above preparation method.

[0029] The present invention provides a method for preparing a red electroluminescent device based on metal nanoclusters. The red electroluminescent device based on metal nanoclusters is constructed by using metal nanoclusters Au6Cu2 and mixed host materials TCTA and OXD-7. The absorption spectrum of the selected metal nanoclusters is highly overlapped with the electroluminescence curve of the host material, and the host-guest energy transfer condition is met. A red light emitting diode with an electroluminescence (EL) peak of 602nm is prepared by using a host-guest mixed solution as an emission layer. The device has a wavelength of 3253cd m -2 The device has a high brightness and a high external quantum yield (EQE) of 1.16%. By sandwiching an ultra-thin electrically inert functional layer of LiF between the emission layer (EmL) and the electron transport layer (ETL), the energy transfer direction of the host material is further standardized, the exciton recombination area is limited, and the device parameters are further improved, with a brightness of 3887 cd m -2 , the external quantum efficiency reaches 1.55%;

[0030] The preparation method provided by the embodiment of the present invention is simple to operate, takes little time, consumes low energy, and has simple process requirements; the prepared red-light electroluminescent device based on metal nanoclusters has significantly improved brightness, high external quantum efficiency, and good device stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 The absorption spectrum and photoluminescence spectrum of the metal nanocluster Au6Cu2 film provided in Example 1 of the present invention are embedded as thin film optical photographs;

[0032] Figure 2 The transient photoluminescence spectrum (TRPL) of the metal nanocluster Au6Cu2 film provided in Example 1 of the present invention and the corresponding fitting curve;

[0033] Figure 3 The photoluminescence quantum yield (PLQY) of the metal nanocluster Au6Cu2 film without and with the host material provided in Example 1 of the present invention;

[0034] Figure 4 The scanning electron microscope image (SEM) and corresponding elemental analysis of the metal nanocluster Au6Cu2 film after the introduction of the host material provided in Example 1 of the present invention;

[0035] Figure 5 The transient absorption spectrum (TA) and the corresponding kinetic fitting curve of the metal nanocluster Au6Cu2 film after the introduction of the host material provided in Example 1 of the present invention;

[0036] Figure 6 A schematic diagram of the energy level structure of a red light electroluminescent device based on metal nanoclusters provided in Example 1 of the present invention, wherein the energy level structure of the metal nanoclusters Au6Cu2 is from literature and Dow diagram;

[0037] Figure 7 Electroluminescence spectra of the red electroluminescent device based on metal nanoclusters provided in Example 1 of the present invention at different bias voltages, with a built-in device of 500 cd m -2 Optical photographs at the time of

[0038] Figure 8 The brightness-voltage-current density curve (JVL) of the red electroluminescent device based on metal nanoclusters under the conditions of different thicknesses of LiF provided in Example 1 of the present invention;

[0039] Fig. 9 The brightness-external quantum efficiency (EQE), current power (CE), and power efficiency (PE) curves of the red electroluminescent device based on metal nanoclusters under the conditions of different thicknesses of LiF provided in Example 1 of the present invention;

[0040] Fig.10 The red electroluminescent device based on metal nanoclusters provided in Example 1 of the present invention has a wavelength of 50 cd m -2 Brightness falloff curve under Luma. DETAILED DESCRIPTION

[0041] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0042] The specific implementation of the present invention is described in detail below in conjunction with specific embodiments.

[0043] Embodiment 1: A red light electroluminescent device based on metal nanoclusters, the preparation method of which comprises the following steps:

[0044] 1) Dissolve 11.0 mg of tetrahydrothiophene gold Au(tht)Cl and 10.0 mg of 4'-ethynylbenzo-15-crown-5 in 20 mL of chromatographically pure dichloromethane solution, and stir at 1000 r / min on a magnetic stirring table for 10 min until fully dissolved;

[0045] 2) Add 20 μL of triethylamine solution as a reaction catalyst at a magnetic stirring table at a speed of 700 r / min, stir for 2.5 h at 0°C, and the speed of the magnetic stirring table is 700 r / min; then use a rotary evaporator to evaporate the solvent, the speed of the rotary evaporator should be 100 r / min, and the temperature should be maintained at 25°C; and redissolve with 3 mL of chromatographically pure dichloromethane solution to obtain an orange-red solution;

[0046] 3) The orange-red solution obtained in step 2) was sealed at 5° C. and crystallized by diffusion using n-hexane. After standing for 96 hours, the orange-red needle-shaped crystals on the inner wall of the container were collected;

[0047] 4) 29.5 mg of the orange-red needle-shaped crystals obtained in step 3) and 5.5 mg of powdered Cu(NCMe)4PF6 were dissolved in 1 mL of chromatographically pure dichloromethane solution, and stirred for 30 min in a dark environment to obtain a transparent red solution, wherein the speed of the magnetic stirring table was 800 r / min;

[0048] 5) The transparent red solution obtained in step 4) is sealed at 0°C and crystallized by diffusion using ether. After standing for 72 hours, the red needle-shaped crystals on the inner wall of the container are collected, which are the metal nanoclusters Au6Cu2;

[0049] 6) Take 2.0 mg of the red needle-shaped crystals obtained in step 5) and dissolve them in 1 mL of chromatographically pure dichloromethane solution containing 4.0 mg of electron acceptor material TCTA and 3.5 mg of electron donor material OXD-7 and stir vigorously for 2 min. After ultrasonic treatment for 1 min, a host-guest mixed solution is obtained;

[0050] 7) Preliminary preparation of cluster red electroluminescent devices modified with host, guest and insulating layer:

[0051] 7.1) Clean the ITO conductive glass with soap, deionized water, ethanol, chloroform, acetone and isopropanol in turn, and perform UV-ozone treatment;

[0052] 7.2) Spin coating a PEDOT:PSS solution (Baytron PVP Al 4083) on the treated ITO glass through a filter head at a spin coating speed of 4000 r / min for 30 s, followed by annealing to obtain a hole injection layer; the substrate was then transferred to a glove box filled with N2 gas, where the annealing temperature was 170°C for 30 min;

[0053] 7.3) Spin-coat the host-guest mixed solution prepared in step 6) on the PEDOT:PSS layer as a light-emitting layer at a spin-coating speed of 3000 r / min and a spin time of 30 s;

[0054] 8) The ultra-thin insulating layer LiF, the electron transport layer PO-T2T, the electron injection layer LiF, and the metal electrode Al were evaporated onto a glass substrate to prepare a red electroluminescent device (diode LED) based on metal nanoclusters, wherein the evaporation rate of ultra-thin LiF, PO-T2T and LiF was 0.1 nm / s, and the final thicknesses were 1.0 nm, 37.5 nm and 1.2 nm, respectively; the evaporation rate of Al was 1 nm / s, and the final thickness was 100 nm.

[0055] Performance Test:

[0056] The metal nanoclusters prepared in Example 1 (i.e., the red needle-shaped crystals obtained in step 5) were converted into thin films by spin coating. The surface flatness of the thin films was good. The absorption spectrum and photoluminescence spectrum were analyzed. Figure 1 As shown, according to Figure 1 It can be seen that the film shows bright orange-red light emission with a peak at 610 nm under 365 nm ultraviolet light excitation, and the characteristic absorption peaks at 310 nm and 400 nm indicate that the metal nanocluster crystals have high purity;

[0057] The transient photoluminescence spectrum of the metal nanocluster film was measured at an excitation wavelength of 375 nm, and the results were as follows Figure 2As shown, according to Figure 2 It can be seen that the double exponential fitting curve is good, showing that its average lifetime is about 2.3μs. The appropriate lifetime indicates that it will not suffer from severe triplet quenching process while ensuring the emission intensity, and is suitable for use as a phosphorescent dopant in electroluminescent devices;

[0058] The metal nanocluster film was compared with the metal nanocluster film after the host material was introduced (i.e., the metal nanocluster was dissolved in a dichloromethane solution containing the electron acceptor material TCTA and the electron donor material OXD-7 in step 6), and the photoluminescence quantum yield results were obtained as follows: Figure 3 As shown, according to Figure 3 It can be seen that the introduction of the host material improves the photoluminescence quantum yield of the metal nanocluster film from 10.19% to 40.56%;

[0059] The metal nanocluster film after the introduction of the main material was analyzed by scanning electron microscopy, and the SEM image and corresponding element analysis were obtained. Figure 4 As shown, according to Figure 4 It can be seen that through the observation of its metal core elements Au and Cu, it is found that the metal nanoclusters are evenly distributed on the film, and the introduction of the main material avoids the concentration quenching caused by excessive accumulation;

[0060] The transient absorption spectrum of the metal nanocluster film after the introduction of the main material was tested, and the results were as follows Figure 5 As shown, according to Figure 5 It can be seen that the main material produces more triplet excited states through fewer singlet excited states, and the dexter energy transfer process occurs;

[0061] The red electroluminescent device based on metal nanoclusters prepared in Example 1 was analyzed, and the device energy level structure was obtained as follows: Figure 6 As shown, the semiconductor energy levels of cluster emitters were determined, and the device structure was designed based on the measured values;

[0062] Electroluminescence spectra of red electroluminescent devices based on metal nanoclusters at different bias voltages are shown in Figure 2. Figure 7 As shown, according to Figure 7 It can be seen that the electroluminescence peak of the device remains stable at 600 to 602 nm from low voltage to maximum brightness voltage;

[0063] The thickness of the ultra-thin LiF insulating layer was adjusted to obtain the brightness-voltage-current density curves of the red electroluminescent device based on metal nanoclusters under different LiF thickness conditions. Figure 8 As shown, the brightness-external quantum efficiency, current power and power density curves are as follows Fig. 9 As shown, according to Figure 8 , Fig. 9 It can be seen that when the LiF thickness is about 1nm, the maximum brightness of the device remains basically unchanged, but the current density decreases significantly, which is due to the electrical inertia of LiF; when the LiF thickness gradually increases to about 2nm, the maximum brightness of the device decreases significantly, and the current density decreases further, which is attributed to the low carrier injection caused by the overly thick insulating layer;

[0064] Red electroluminescent devices based on metal nanoclusters at 50 cd m -2 The brightness attenuation curve results under brightness are as follows Fig.10 As shown, according to Fig.10 It can be seen that the brightness of the device decays more slowly after the introduction of LiF, and the stability of the device is improved. This is because the low current density causes it to suffer less Joule heating effect.

[0065] In summary, the present invention uses metal cluster Au6Cu2 and host materials TCTA and OXD-7 to prepare a red electroluminescent device based on metal nanoclusters. The introduction of the host material brings about the Dexter energy transfer process, which enhances the luminescence of the metal nanoclusters. By flexibly referring to the electrically inert LiF insulating layer between the EML and the ETL, the energy transfer path is further standardized and the exciton recombination area is limited. The host-guest system is used as the emission layer to prepare a red organic light-emitting diode with an electroluminescence (EL) wavelength of 602nm. The device has a wavelength of 3887cd m -2 At the same time, the introduction of LiF significantly reduces the current density, significantly improves the device stability, and the brightness decay time is about 3 times that when LiF is not introduced.

[0066] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a red light electroluminescent device based on metal nanoclusters, characterized in that: The following steps are involved: S1. Dissolve tetrahydrothiophene gold and 4'-ethynylbenzo-15-crown-5 in dichloromethane solution and stir until completely dissolved; S2, dropwise adding triethylamine solution, stirring at low temperature, evaporating the solvent and re-dissolving it with dichloromethane solution to obtain an orange-red solution; S3, sealing the orange-red solution at low temperature, using n-hexane for diffusion crystallization, and collecting the orange-red needle-shaped crystals after standing; S4, dissolving the orange-red needle-shaped crystals and powdered Cu(NCMe)4PF6 in a dichloromethane solution, stirring in the dark to obtain a transparent red solution; S5, seal the transparent red solution at low temperature, diffuse and crystallize it with ether, and collect the red needle-shaped crystals after standing; S6, dissolving the red needle-shaped crystals in a dichloromethane solution containing an electron acceptor material TCTA and an electron donor material OXD-7 to obtain a host-guest mixed solution; S7. Preliminary preparation of cluster red electroluminescent devices modified with host, guest and insulating layer: S71, cleaning the ITO conductive glass and performing ultraviolet ozone treatment; S72, spin coating a PEDOT:PSS solution on the ITO glass, annealing the solution to obtain a hole injection layer, and then transferring the solution to a glove box filled with N2 gas; S73, spin coating the host-guest mixed solution on the PEDOT:PSS layer as a light-emitting layer; S8. Transfer the product obtained in S7 into a vacuum chamber, and deposit ultra-thin LiF, PO-T2T, LiF and Al layers in sequence by thermal evaporation, wherein the ultra-thin LiF serves as an insulating layer, the PO-T2T layer serves as an electron transport layer and a hole blocking layer, and the LiF and Al layers serve as top electrodes, thereby obtaining the red electroluminescent device based on metal nanoclusters.

2. The method for preparing a red light electroluminescent device based on metal nanoclusters according to claim 1, characterized in that: In S1, the stirring speed is 800-1000 r / min, and the time is 8-10 min.

3. The method for preparing a red light electroluminescent device based on metal nanoclusters according to claim 1, characterized in that: In S2, the stirring speed is 600-800 r / min, and the volatile solvent is evaporated using a rotary evaporator with a speed of 80-100 r / min and a temperature of 23-28°C.

4. The method for preparing a red light electroluminescent device based on metal nanoclusters according to claim 1, characterized in that: In S4, the stirring speed is 800-1000 r / min.

5. The method for preparing a red light electroluminescent device based on metal nanoclusters according to claim 1, characterized in that: In S6, the concentration of red crystals in the host-guest mixed solution is 2.0 mg / mL, the concentration of TCTA is 4.0 mg / mL, and the concentration of OXD-7 is 3.5 mg / mL; After the step of dissolving the red needle-shaped crystals in the dichloromethane solution containing the electron acceptor material TCTA and the electron donor material OXD-7, the method further includes the steps of vigorous shaking for 1-2 minutes and ultrasonication for 1-2 minutes.

6. The method for preparing a red light electroluminescent device based on metal nanoclusters according to claim 1, characterized in that: In S71, the step of cleaning the ITO conductive glass is specifically: cleaning the ITO conductive glass with soap, deionized water, ethanol, chloroform, acetone and isopropyl alcohol in sequence.

7. The method for preparing a red light electroluminescent device based on metal nanoclusters according to claim 1, characterized in that: In S72, the rotation speed of the spin coating PEDOT:PSS solution is 3800-4200 r / min, and the rotation time is 28-32 s; The annealing treatment is performed at a temperature of 165-175° C. and for a time of 25-35 minutes.

8. The method for preparing a red light electroluminescent device based on metal nanoclusters according to claim 1, characterized in that: In S73, the rotation speed of spin coating the host-guest mixed solution on the PEDOT:PSS layer is 2800-3200 r / min, and the rotation time is 38-32 s.

9. The method for preparing a red light electroluminescent device based on metal nanoclusters according to claim 1, characterized in that: In S8, the evaporation rates of the ultra-thin LiF, PO-T2T and LiF are 0.05-0.2 nm / s, and the thicknesses are 0.5 nm-2 nm, 30-50 nm and 1-2 nm respectively; the evaporation rate of Al is 1-3 nm / s, and the thickness is 100-120 nm.

10. A red electroluminescent device based on metal nanoclusters prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method for preparing LEDs with different light colors based on metal nano-cluster packaging material

    CN105304799A

  • Electroluminescent device comprising metal nanocluster

    CN106257703A

  • AuCu14 nanocluster with high phosphorescent quantum yield in air atmosphere, and preparation method of AuCu14 nanocluster

    CN112110955A

  • Gold cluster-copper cluster composite microsphere with long service life and strong luminescence as well as preparation method and application of gold cluster-copper cluster composite microsphere

    CN117505837A

  • Light emitting diode, preparation method thereof and display device

    CN118265320A